First Evidence of Bottom-Based Construction in South America. The ‘Sin Nombre’ Canoe at the Port of Honda, Tolima, Magdalena River, Colombia - Borrero L, Ricardo (The international journal of nautical archaeology, 2025)
This paper presents the first systematic documentation of bottom-based construction in South America. Employing updated methodologies, we recorded the construction of the ‘Sin Nombre’ canoe, which was crafted by Master Wilson Ospina Riocampos off the banks of the Magdalena River in Honda, Tolima, Colombia, in June 2023. The article engages with existing literature, discusses various theoretical and methodological aspects of bottom-based and/or bottom-first construction, and offers a comprehensive description of the materials, tools, and the entire process involved in conceiving, designing, and constructing the canoe.